& co-graphy. Issue 1 (July 2019) - Dutoit, Thomas
Abstract : & co-graphy names here writing experienced as differance of 'now' ('the present') and 'then' ('the past', 'the future'), of memory and erasure called here 'saw' and 'was' and the rupture that constitutes them. & co-graphy also brings into dialogue Elizabeth Bowen's novel The Little Girls, explicitly writing the theme of extinction through reflection upon global-scaled destructions (World War 1, nuclear holocaust and winter, climate change), with poet W. S. Merwin's longstanding engagement with the 'environment' and disappearing forms of life and culture.